Evaluating the parameters influencing agricultural productivity due to the limitations of smartphone-related knowledge among farmers - Angon, Prodipto Bishnu; Khan, Md. Mahbubur Rahman; Islam, Md. Shafiul; Suma, Rucksana Parvin; Habiba, Ummya (Archives of Agriculture and Environmental Science, 2022)
The use of smartphones has improved individuals significantly in this age of information technology. Yet farmers cannot use this smartphone due to a lack of proper knowledge. Where smartphones could easily be used by farmers to solve their agricultural problems. The aims of the study to improve the daily life of a farmer as well as to gain skills in the use of smart phones. Nine characters have been selected to find out the relation between knowledge of farmers’ use of smartphones in agriculture. The data are collected through interviews from 128 farm families from Mymensingh of Bangladesh. A semi-structured questionnaire is distributed for collecting data. Those data were pre-arranged and categorized by using M.S. Excel. Spearman’s Rank Order were used to create correlations among the characteristics of farmers. Among the selected farmers 56% have low knowledge and only 3% of farmers have high knowledge about the use of smartphones in the agricultural sector. Among nine characters ages and firm experience have a strong negative significant correlation (-0.548* and -0.541*, respectively). On the other hand, extension media interaction has a strong positive relationship (0.588*). From this output, farmers will be able to gain a complete understanding of smartphones to solve the agricultural problems with proper training and experience.